Vehicles and Infrastructure for Emission-Free Operation on Non-Electrified Lines (Current Problems in Rail Vehicles, 2021)
The transition of the Czech railways to fully emission-free operation is an objective necessity. And not only to save energy and emissions, but also to increase the efficiency and effectiveness of rail transport. It appears reasonable to do this by combining line and battery power to the vehicles. The renewal of the vehicle fleet needs to be coordinated with the development on the railway infrastructure side. With the conversion of track power supply from 3 kV to 25 kV, the development of line and point electrification and the introduction of ETCS on lines and vehicles.
Keywords: electrification; hybrid vehicles; zero emission operation; hydrogen